2020
DOI: 10.1186/s12967-020-02327-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes in papillary thyroid carcinoma: robust rank aggregation and weighted gene co-expression network analysis

Abstract: Background: Papillary thyroid carcinoma (PTC), which is the most common endocrine malignancy, has been steadily increasing worldwide in incidence over the years, while mechanisms underlying the pathogenesis and diagnostic for PTC are incomplete. The purpose of this study is to identify potential biomarkers for diagnosis of PTC, and provide new insights into pathogenesis of PTC.Methods: Based on weighted gene co-expression network analysis, Robust Rank Aggregation, functional annotation, GSEA and DNA methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Hub genes are genes that play crucial roles in biological processes. We constructed the coexpression network of overlapped DEGs to screen KIRC-related hub genes according to previous reports [ 49 , 50 ], and the results showed that both PGK1 and CXCR4 are KIRC-related hub genes and highly expressed in KIRC tissues, and there is a strong interaction between PGK1 and CXCR4. The KIRC clinical samples with high mRNA level of PGK1 often own high mRNA expression of CXCR4 correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…Hub genes are genes that play crucial roles in biological processes. We constructed the coexpression network of overlapped DEGs to screen KIRC-related hub genes according to previous reports [ 49 , 50 ], and the results showed that both PGK1 and CXCR4 are KIRC-related hub genes and highly expressed in KIRC tissues, and there is a strong interaction between PGK1 and CXCR4. The KIRC clinical samples with high mRNA level of PGK1 often own high mRNA expression of CXCR4 correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…Zhai et al collected data for 10,428 genes and obtained three modules associated with N staging, including 11 recurrence‐related genes 19 . Using the Gene Expression Omnibus (GEO) database, Liu et al screened staging‐related hub genes by WGCNA and further showed that these hub genes were correlated with DNA methylation and tumor‐infiltrating immune cells 20 . Tang et al used WGCNA to identify five hub genes related to the progression of PTC within GSE27155 21 .…”
Section: Discussionmentioning
confidence: 99%
“…To identify the differentially expressed mRNA (DEmRNA) in MM, the SVA package was used to remove the batch effect of the microarray data, and microarrays from the same platform were integrated. The Limma package was used for differential expression analysis of the mRNA expression profiles of each platform, and the DEmRNA in MM was obtained by the Robust Rank Aggregation method 15‐18 …”
Section: Methodsmentioning
confidence: 99%